A simplified model connecting lattice distortion with friction stress of Nb-based equiatomic high-entropy alloys. Issue 8 (3rd August 2019) - Zhao, Y. Y.; Lei, Z. F.; Lu, Z. P.; Huang, J. C.; Nieh, T. G.
ABSTRACT: We conducted systematically tensile tests with a series of Nb-based equiatomic alloys with single-phase, body-centered-cubic (bcc) structure. By subtracting all possible strengthening contributions, the intrinsic strength (or lattice friction stress) of each alloy was extracted. It was found that lattice friction stress scaled linearly with the lattice distortion in these Nb-based alloys. A simple model was developed to interpret this result. Strengthening effects of lattice distortion and dislocation core width between bcc Nb-based and face-centered-cubic (fcc) Ni-based equiatomic alloys were also compared. It was demonstrated that the enhanced strength in high-entropy alloys was attributable to the lattice distortion. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Lattice friction stress in equiatomic alloys correlates linearly with the lattice distortion, quantitatively defined as the average lattice strain. A simple physical model was developed to interpret this result.